Efektivitas E-Modul Fisika Berbasis Inquiry Terbimbing Berbantuan Simulasi PhET terhadap Hasil dan Minat Belajar Siswa - Azis, Muhammad; Ariani, Tri (U-Teach: Journal Education of Young Physics Teacher, 2025)
This study examines the effectiveness of physics e-modules designed with a guided inquiry approach and supported by PhET simulations in enhancing students’ learning outcomes and learning interest. A Systematic Literature Review (SLR) was conducted by gathering studies indexed in Scopus, Google Scholar, Garuda, and SINTA between October 10 and November 12, 2025. From 87 studies identified, the PRISMA filtering process selected 50 articles that met all eligibility criteria. Rayyan software was used for screening, Mendeley for reference management, and Excel for descriptive analysis. The review indicates that 84% of the studies reported improved learning outcomes, 78% noted increased learning interest, and 66% showed simultaneous improvement in both variables. These results are influenced by the structured phases of guided inquiry, the interactive design of e-modules, and the visual dynamics of PhET simulations. Future research is encouraged to broaden thematic focus and examine moderating variables for deeper analytical insights